汉语综合课词汇教学法分析 - Ina Ina (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
Comprehensive Chinese is a core course in the Chinese language education majoring program, accounting for 40% of the total credit load in a single semester. Among the four main components of language, vocabulary plays a fundamental role as both a building block of language and a gateway to learning Mandarin.This study employs a qualitative approach, utilizing data collection methods such as classroom observation, interviews with instructors, and student questionnaires. The aim is to evaluate the vocabulary teaching methods used in the second-semester Comprehensive Chinese course within the Mandarin Language Education Program at the Faculty of Teacher Training and Education, Tanjungpura University. This research is significant in providing deeper insight into the effectiveness of chinese vocabulary instruction and contributing to the development of innovative teaching approaches. The findings indicate that students responded positively to the vocabulary teaching methods and media used, particularly the use of images and slides. It can therefore be concluded that the integration of diverse teaching methods, including more active interaction and in-depth explanations, can enhance students’ vocabulary comprehension in Chinese language learning.